SMART HOME AUTOMATION TOWARDS THE DEVELOPMENT OF SMART CITIES - Alam, Tanweer; Salem, Abdulrahman A.; Alsharif, Ahmad O.; Alhejaili, Abdulaziz M. (APTIKOM Publisher, 2020)
Home automation system is a system that controls by the smart device using a mobile application. It can control home appliances such as light, fans, air conditions, and smart security locks, etc. Bluetooth or Wi-Fi technology will be used to control things remotely.  Many people were thinking about that technology is taking a really huge part of our lives. It does! we?re living in a modern generation where smart and intelligent systems are necessary to be there wherever we are to make our lives easier and much better, for example, we can do many things faster, better, and more accurate.